Pembinaan Keluarga Dalam Pencegahan Stunting Pada Anak - Yollanda Dwi Santi Violentina; Suryani Suryani; Dona Martilova; Susani Hayati (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2023)
Stunting is one of the problems that hinders human development globally. The prevalence of stunting in Riau Province showed a decrease from 23.7% to 27.4%, with the number of babies experiencing stunting in Pekanbaru City reaching as many as 1,248 toddlers. This community service activity aims to increase family knowledge about stunting and its prevention. The method used in this community service is carried out online; the implementation of activities is carried out starting from the establishment of a family counseling platform, especially for pregnant women, which is made in the form of whatsapp groups and webinars, which are carried out using the Zoom meeting application, and activities are carried out for three months, namely November 2020 to January 2021. This community service activity received a positive response from the community, as evidenced by the many pregnant women who asked about the masteries presented and enthusiastically shared their pregnancy experiences. It can be concluded that pregnant women's knowledge about stunting increases, as evidenced by the increase in post-test scores. It is hoped that the puskesmas will actively provide counseling and invite pregnant women and mothers with toddlers to routinely have health checks for early detection and to prevent stunting.